Making Use of Competitive Advantages of a University Education Innovation Cluster in the Educational Services Market - Gryshchenko, Ivan; Ganushchak-Efimenko, Lyudmila; Shcherbak, Valeriia; Nifatova, Olena; Zos-Kior, Mykola; Hnatenko, Iryna; Martynova, Liliia; Martynov, Andrii (European Journal of Sustainable Development, 2021)
One of the major trends of the contemporary world market of educational services is the increasing role of knowledge and information in socioeconomic development, when knowledge becomes a key driver of economic prosperity and competitiveness as well as a critical factor in boosting the labour market demand for a new type of skilled workforce which gives rise to a sweeping demand for professional higher education, incrementally demanding requirements to Universities in terms of meeting social needs, and the globalization of the world economy. Such drastic development dynamics of University environment along with the objective escalation of competition in the area of educational services greatly affect the issues of strategic planning and University competitiveness management in the long run.